Correction: Watanabe et al. Pemafibrate Improves Alanine Aminotransferase Levels Independently of Its Lipid-Lowering Effect. Livers 2023, 3, 562–568 - Azuma Watanabe; Ryoko Horigome; Yumiko Nakatsuka; Shuji Terai (Livers)
In the original publication [...]